If we had wings we would fly to you: a Soviet Jewish Family faces destruction, 1941-42 - Feferman, Ḳiril (Jews of Russia and Eastern Europe and their legacy, 2020)
Historical Background -- The Ginsburg Family in the North Caucasus -- Soviet Population Evacuation into the North Caucasus, 1941-42 -- The Holocaust in the North Caucasus -- The Ginsburg Family Correspondence -- 1941 -- 1942-43.